Analisis Tingkat Kepuasan Karyawan Terhadap Lingkungan Kerja Di PT Qualis Indonesia Dengan Metode Customer Satisfaction Index : Analysis of Employee Satisfaction Levels with the Work Environment at PT Qualis Indonesia Using the Customer Satisfaction Index Method - Nurul Hidayah; Ratih Hastasari (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to analyze the level of employee satisfaction toward the work environment at PT Qualis Indonesia using the Customer Satisfaction Index (CSI) method. Employee satisfaction is an important factor that influences productivity, loyalty, and organizational performance. The work environment, which includes physical and non-physical aspects, plays a strategic role in shaping employee satisfaction. The research method used is a descriptive quantitative approach with primary data obtained through the distribution of questionnaires to employees of PT Qualis Indonesia. The number of respondents in this study was 67 employees from operational and administrative divisions. The data analysis technique was conducted by calculating the Customer Satisfaction Index (CSI) to determine the overall level of employee satisfaction and to identify work environment attributes that most influence satisfaction. The results of the study indicate that the level of employee satisfaction toward the work environment at PT Qualis Indonesia falls into the satisfied category. However, several work environment attributes still need improvement, particularly related to work facilities, workload, and internal communication. The results of this study are expected to serve as evaluation material for management in improving the quality of the work environment and as a reference for future research related to measuring employee satisfaction using the CSI method.